2020
DOI: 10.1111/gwao.12484
|View full text |Cite
|
Sign up to set email alerts
|

Caring during COVID‐19: A gendered analysis of Australian university responses to managing remote working and caring responsibilities

Abstract: COVID‐19 is dramatically reconfiguring paid work and care. Emerging evidence in the global media suggests that academic women with caring responsibilities are being disproportionately impacted. This article fills a key knowledge gap by examining how Australian universities are supporting academics to manage remote work and caring during the COVID‐19 pandemic. We conducted a desktop analysis of public information about remote working and care from 41 Australian universities and compared them to the world’s top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(182 citation statements)
references
References 35 publications
5
172
0
5
Order By: Relevance
“…Staff underlined the importance of improving supervisory capacity through information, resources and training, to support more consistent practice across the institution. This is consistent with previous research that has found FWAs usually need to be individually negotiated, failing to recognise that the need for FWAs is often not a matter of individual choice (Nash & Churchill, 2020). Consistency in access to FWAs across work units in post-COVID contexts is worthy of further monitoring and research, as it not yet clear how the 'unevenness' in managerial mindset and capacity identified by staff in the focus groups have been manifest in the context of the COVID-19 pandemic.…”
Section: Concluding Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Staff underlined the importance of improving supervisory capacity through information, resources and training, to support more consistent practice across the institution. This is consistent with previous research that has found FWAs usually need to be individually negotiated, failing to recognise that the need for FWAs is often not a matter of individual choice (Nash & Churchill, 2020). Consistency in access to FWAs across work units in post-COVID contexts is worthy of further monitoring and research, as it not yet clear how the 'unevenness' in managerial mindset and capacity identified by staff in the focus groups have been manifest in the context of the COVID-19 pandemic.…”
Section: Concluding Discussionsupporting
confidence: 81%
“…While the salience of gender in participants' accounts is somewhat unsurprising, it serves as a reminder of the ways university structures create unequal opportunities across gender, seniority and roles, and the contradictions of seeking gender equality through gendered flexibility practices. Whether and how the expansion of flexibility in 2020 disrupts patterns of gendered use of flexibility is not yet evident, however, early evidence (Nash & Churchill, 2020) indicates the pandemic is disproportionately impacting on women with caring responsibilities, with universities providing little guidance about working remotely or with children during Overall, the experiences and perceptions shared by staff prior to the pandemic provide insight into directions for change in the emerging higher education landscape. While higher education -like other sectors -has placed an increasing emphasis on employee wellbeing and increased opportunities for FWAs in recent years, it is not yet clear how the tensions evident prior to the pandemic will manifest.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The first was a personal reflection on social isolation and struggles of working from home for single women living alone and how technology helped them to connect with colleagues (Gao & Sai, 2020). The second study was a desktop analysis of the websites of Australian universities and how they support academic staff with caring responsibilities (Nash & Churchill, 2020).…”
Section: Remote E-working and Covid-19mentioning
confidence: 99%
“…Nash and Churchill raise the interesting subject of academic women's occupation during the pandemic [8]. It is observed that women's publication track records have decreased significantly, even by 50% in some areas.…”
Section: Global Education Policiesmentioning
confidence: 99%